2000
DOI: 10.1021/ol005573v
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant SRN1 Reaction of 4-Aminophenol with α,p-Dinitrocumene:  EPR Observation of Intermediates

Abstract: The tert-butoxide-induced substitution of alpha,p-dinitrocumene by 4-aminophenol unexpectedly afforded the N-coupled product, 2-(4-hydroxyanilino)-2-(4-nitrophenyl)propane. EPR observations revealed arylaminyl radical intermediates as well as coupled anion radicals, hence the normal S(RN)1 process may compete with an alternative nonchain reaction pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Recently, substitution via nitrogen was reported in the base-induced reaction of p -H 2 NC 6 H 4 OH with α, p -dinitrocumene. The ESR observation of the aryl aminyl radical and of the radical anion of the substitution product suggested that an S RN 1 process might be accompanied by an alternative path, which involves combination of the phenoxide aminyl with the 4-nitrocumyl radical 13 Photoinduced Reactions of p -Nitrobenzyl and p -Nitrocumyl Derivatives with Nitrogen-Centered Nucleophiles in DMSO a a X as leaving group.…”
Section: B Nitrobenzyl and Cumyl Derivatives1 P-nitrobenzyl And Cumyl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, substitution via nitrogen was reported in the base-induced reaction of p -H 2 NC 6 H 4 OH with α, p -dinitrocumene. The ESR observation of the aryl aminyl radical and of the radical anion of the substitution product suggested that an S RN 1 process might be accompanied by an alternative path, which involves combination of the phenoxide aminyl with the 4-nitrocumyl radical 13 Photoinduced Reactions of p -Nitrobenzyl and p -Nitrocumyl Derivatives with Nitrogen-Centered Nucleophiles in DMSO a a X as leaving group.…”
Section: B Nitrobenzyl and Cumyl Derivatives1 P-nitrobenzyl And Cumyl...mentioning
confidence: 99%
“…The ESR observation of the aryl aminyl radical and of the radical anion of the substitution product suggested that an S RN 1 process might be accompanied by an alternative path, which involves combination of the phenoxide aminyl with the 4-nitrocumyl radical. 297 Oxygen and Sulfur Nucleophiles. Oxygen nucleophiles afford O-alkylation not only with R-substituted nitroalkanes 285 but also with p-nitrocumyl derivatives 45,63,121 by the S RN 1 mechanism.…”
Section: P-nitrobenzyl and Cumyl Derivativesmentioning
confidence: 99%
“…Although the radical chain process could be partially attained through iodine radical abstraction from 14 by 20 to form iodomethylcyclopantane 21 , that is converted into 18 . However, formation of the C­(sp 3 )–N bond with these radical intermediates does not occur in this case, while they strongly abstract a hydrogen from the solvent [tetrahydrofuran (THF)] …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this reaction occurred smoothly in the presence of either TEMPO or BHT and the yield was not changed. This result might suggest that no radical species exists during the reaction, though a nitrogen nucleophile can react with a tert ‐alkyl radical to produce tert ‐alkylamines by an S RN 1‐like reaction . We also examined the amount of amine and found that the amination occurred smoothly with either 3 or 1.5 equivalents of 2 a at room temperature (entries 14 and 15).…”
Section: Figurementioning
confidence: 99%